Maia type fixed point results for multivalued F-contractions - Olgun, Murat; Alyıldız, Tuğçe; Biçer, Özge; Altun, İshak (University of Miskolc, Institute of Mathematics, 2021)
In this paper, by considering the Wardowski's technique, we present fixed point results for multivalued mapping on a space with two metrics. Also, taking into account a-admissibility of a multivalued mapping, we provide some more general results.
Keywords: Fixed Point; Multivalued F-Contractions; Complete Metric Space